Electrochemical Aziridination by Alkene Activation Using a Sulfamate as the Nitrogen Source. (20th April 2018) - Li, Jin; Huang, Wenhao; Chen, Jingzhi; He, Lingfeng; Cheng, Xu; Li, Guigen
Abstract: The first direct aziridination of triaryl‐substituted alkenes was achieved by means of an electrochemical process that could extend to multisubstituted styrenes. Specifically, hexafluoroisopropanol sulfamate was used as a nucleophilic nitrogen source. Mechanistic experiments suggest that this electrochemical process proceeds by stepwise formation of two C−N bonds through reactions between cationic carbon species and the sulfamate.